2006
DOI: 10.1016/j.febslet.2006.07.037
|View full text |Cite
|
Sign up to set email alerts
|

The control of UCP1 is dissociated from that of PGC‐1α or of mitochondriogenesis as revealed by a study using β‐less mouse brown adipocytes in culture

Abstract: In rodent brown adipose tissue, the b-adrenergic signaling is believed, by an action on PGC-1a, to control UCP1 expression and mitochondriogenesis. We addressed this hypothesis using b 1 /b 2 /b 3 -adrenoceptor knockout (b-less) brown adipocytes in primary culture. In these cells: (a) proliferation and differentiation into multilocular cells were normal; (b) UCP1 mRNA expression was dramatically decreased (by 93%), whereas PGC-1a and mtTFA mRNA expressions were not; (c) UCP1, PGC-1a and COX IV protein expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 31 publications
3
12
0
1
Order By: Relevance
“…Concerning UCP1 in BAT, we observed that this parameter is lower in b-less than in WT animals, an observation in keeping with previously reported results. 27 As was observed in WT mice, food restriction had no effect on BAT UCP1 expression in b-less animals. The situation is different for BAT D2 expression, as we observed that food restriction failed to promote a decrease in this parameter in b-less mice as it does in WT mice.…”
Section: Control P-f Leptinsupporting
confidence: 51%
“…Concerning UCP1 in BAT, we observed that this parameter is lower in b-less than in WT animals, an observation in keeping with previously reported results. 27 As was observed in WT mice, food restriction had no effect on BAT UCP1 expression in b-less animals. The situation is different for BAT D2 expression, as we observed that food restriction failed to promote a decrease in this parameter in b-less mice as it does in WT mice.…”
Section: Control P-f Leptinsupporting
confidence: 51%
“…However, Petrovic et al (27) recently showed that a proportion of mitochondrion-rich cells are UCP-1 positive, whereas numerous mitochondrion-rich cells are negative for UCP-1 during the induction of brown adipocytes in WAT by PPAR-␥ activation. A recent study also showed that, in a primary culture of ␤-adrenoceptor knockout brown adipocytes, UCP-1 mRNA expression level is markedly decreased, whereas PGC-1␣ and TFAM mRNA expression levels are not (23). Moreover, in the same experiment, UCP-1, PGC-1␣, and COX IV protein expression levels are decreased by 97, 62, and 22%, respectively.…”
Section: Discussionmentioning
confidence: 63%
“…PPARγ coactivator 1α (PGC-1a) is a PPARγ interacting protein and is restricted to oxidative tissues including BAT and skeletal muscle [32]. It is observed that cold and /or adrenergic stimulation increases the expression of this gene in BAT and then induces elevated expression of UCP1 [33], [34]. The heart-type fatty acid-binding protein (FABP3) is essential for efficient brown adipose tissue fatty acid oxidation and cold tolerance.…”
Section: Discussionmentioning
confidence: 99%